Empathy (Political Emotion) - Seoane Pinilla, Julio (EUNOMÍA. Revista en Cultura de la Legalidad, 2024)
This article presents the state of the art on the concept of empathy as a tool for the field of morality and politics. It will begin by giving an account of the reasons that have led us to speak of empathy since the beginning of the 21st century, showing the elements for and against its moral use and the kind of social relationships it promotes. After having shown that empathy is not really an emotion but a mechanism of affective communication, it will end with a brief assessment that (a) recognises that, although it is common to adopt the concept of empathy together with notions of justice (to soften rational argumentation), empathy implies a completely different world from the one our conceptions of justice are usually used, and (b) that the process of empathy, although it may start as a “natural affection”, needs an voluntary effort of fine-tuning and education.